2013
DOI: 10.3109/10715762.2013.783210
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor exhibits an antioxidant and an autocrine activity in mouse liver that is modulated by buthionine sulfoximine, arsenic, and acetaminophen

Abstract: Nerve growth factor (NGF) is one of the several structurally related proteins, named neurotrophins (NTs), that regulate neuronal survival, development, function, and plasticity. Moreover, NGF is an important activator of antioxidant mechanisms. These NGF functions are mediated by tropomyosin-related kinase receptor A (TrkA). Although NTs and their receptors have been shown to be expressed in visceral tissues, the extent to which NTs are involved in the physiology of visceral tissues is less clear. NGF is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
3
20
1
Order By: Relevance
“…Furthermore, Galeotti put forward that NGF‐mediated decrease of mitochondrial ROS was dependent on the transcriptional up‐regulation of the MnSOD by activating CREB. Valdovinos‐Flores and Gonsebatt revealed that NGF played a critical role in liver protection against oxidative stress through maintaining a reduced thiol state. Also, He and Katusic reported a novel finding that BDNF protected human early endothelial progenitor cells by increasing expression of Mn‐SOD to enhance their antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Galeotti put forward that NGF‐mediated decrease of mitochondrial ROS was dependent on the transcriptional up‐regulation of the MnSOD by activating CREB. Valdovinos‐Flores and Gonsebatt revealed that NGF played a critical role in liver protection against oxidative stress through maintaining a reduced thiol state. Also, He and Katusic reported a novel finding that BDNF protected human early endothelial progenitor cells by increasing expression of Mn‐SOD to enhance their antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they can also promote cellular survival, elongation of axons, and myelination of oligodendrocytes and their precursors, in vitro and in lesional paradigms (Linker et al, 2009). Nerve growth factor (NGF) is an important activator of antioxidant mechanisms in neural tissues (Valdovinos-Flores and Gonsebatt, 2013). Brain derived neurotrophic factor (BDNF) can decrease oxidative stress and apoptosis in developing hypothalamic neuronal cells (Boyadjieva and Sarkar, 2013).…”
Section: Brain-derived Neurotrophic Factor and Nerve Growth Factor Atmentioning
confidence: 99%
“…However, systemic activation of this pathway could induce GSH synthesis in other brain regions such as the cortex and cerebellum at 24 h and 9 days ( Figures 1C,D). Increased levels of GSH were observed in mouse brain homogenates (Limón-Pacheco et al, 2007) and in the cerebellum at 2 h after the administration of L-buthionine-S-R-sulfoximine (BSO), a systemic inhibitor of GSH synthesis, which diminished GSH levels in the liver and kidneys (Limón-Pacheco et al, 2007;Valdovinos-Flores and Gonsebatt, 2013;Garza-Lombó et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that NFκB inhibitors diminish the expression of EAAC1 in rats (Tai et al, 2008). Nrf2 and NFκB upregulate the transcription of the nfe2l2 and iκκbα genes, respectively (Valdovinos-Flores and Gonsebatt, 2013;Tonelli et al, 2018) and are considered redox-sensitive switches that activate cellular responses to oxidative stress (Moldogazieva et al, 2018). To investigate whether the activation of these transcription factors was associated with increased amino acid transporter expression and increased GSH levels at 24 h, we measured the transcription of the nfe2l2 and iκκbα genes by quantitative reverse transcription PCR (RT-PCR) at 2, 6 and 24 h in the cortex region.…”
Section: Increased Transcription Of Nfe2l2 and Iκκbα At 6 H Suggests mentioning
confidence: 99%